2020
DOI: 10.1002/wcms.1491
|View full text |Cite
|
Sign up to set email alerts
|

The MolSSI QCArchive project: An open‐source platform to compute, organize, and share quantum chemistry data

Abstract: The Molecular Sciences Software Institute's (MolSSI) Quantum Chemistry Archive (QCArchive) project is an umbrella name that covers both a central server hosted by MolSSI for community data and the Python‐based software infrastructure that powers automated computation and storage of quantum chemistry (QC) results. The MolSSI‐hosted central server provides the computational molecular sciences community a location to freely access tens of millions of QC computations for machine learning, methodology assessment, f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 60 publications
0
62
0
Order By: Relevance
“…The torsion scans shown in Figure 11 were run on QCArchive [18]. They were computed with TorsionDrive [20] and geomeTRIC [54], as standalone geometry optimizer interfaced with the QCEngine [55] project.…”
Section: Detailed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The torsion scans shown in Figure 11 were run on QCArchive [18]. They were computed with TorsionDrive [20] and geomeTRIC [54], as standalone geometry optimizer interfaced with the QCEngine [55] project.…”
Section: Detailed Methodsmentioning
confidence: 99%
“…Formally, M ≤ 4 for hybrid DFT, although modern implementations of hybrid DFT scale asymptotically as N 2.2–2.3 [16]. Using QCArchive data [17,18], we found that empirically, hybrid DFT grows like N 2.6 for the DZVP basis [15] as shown for gradient evaluations in Figure 1, A. To achieve good sampling of the torsion profiles for adequate potential fits, constrained geometry optimizations need to be calculated at ≤ 15 0 intervals, for a minimum of 24 constrained geometry optimizations for a 1D torsion profile.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum chemical calculations (geometry optimizations and torsion scans) were performed on a distributed set of high-performance computing clusters using the MolSSI QCFractal [41] distributed quantum chemistry engine, with results deposited in the public MolSSI QCArchive Server (MQCAS) [42,43] to allow open public access to all data. We used a single level of theory for all QM calculations, B3LYP-D3(BJ) / DZVP [44][45][46][47].…”
Section: Selection Of Quantum Chemistry Methodologymentioning
confidence: 99%
“…What is the future direction of IOData? We aim to support parsing and writing additional file formats, and also to extend our support for writing input files and enable direct integration with QCEngine 21 . Our current to‐do list for IOData can be found on its GitHub's issue page, and we anticipate that most items will be resolved by the end of 2020.…”
Section: Frequently Asked Questionsmentioning
confidence: 99%